Experimental characterization of a new sustainable sand concrete in an aggressive environment - Mohammed Mani; Meriem Fakhreddine Bouali; Abdelouahed Kriker; Abdelkader Hima (Fracture and Structural Integrity)
The scarcity of building materials and the shortage of coarse aggregates which represents the main component of concrete is a problem in the most third world countries, especially in the vast desert areas in Algeria.  In desert conditions where the environment suffers from the phenomenon of rising water and aggressive soil; the evaluation of existing abundant Sand Dune and its compensation for naturel Sand could be a very good economic solution. Several researches at the local and the global levels confirm that Sand Dune can be exploited in concrete after a granular correction. In this paper, a new Sand resource (Oued El-Ratm, El Oued-Algeria) is proposed as an alternative of natural Sand to perform a Sand Concrete. The findings of this experimental study show that the Sand Concrete based on this new resource of sand dune of the Algerian desert has a good resistance when used in the ambient Saharan aggressive conditions.